Desenvolvimentismo e educação: o ensino médio no período de 1956 a 1961 - Ramos, Denise de Amorim (Universidade Federal de São Carlos, 1999)
The government proposals for education, between the years 1956-61, appear linked to the idea that the educational system should be intrinsically linked to the set of structural reforms that were necessary to overcome the conditions of underdevelopment. With the consolidation of the industrial sector and the intention of accelerating economic development, the government, in those years, applied the policy identified with the economic model of association of capitals. The goals program, an instrument of the economic policy of the Juscelino Kubitschek government, referred essentially to the importance of the entry of capital, of foreign technology in the country for the construction of the Brazilian economy, and mainly for the realization of its projects. Comprising thirty sectors, this program highlighted the goals related to the economy: energy, transport, food, basic industry - including, in the last goal, the training program for technical personnel - capable of providing the infrastructure and superstructure for the transformation of the economic structure. The targets program led to a substantial modification, in the political sense, of Brazilian economic development. The nationalist ideology, assumed in previous years by a nationalist economic policy, was formulated contradictorily through the conditions of economic dependence. The national-developmentalist ideology proclaimed in this period was constituted in the Superior Institute of Brazilian Studies (ISEB), which was granted as a nucleus of great importance for the advice of the government of Juscelino Kubitschek. In other words, the developmental thinking of the Instituto Superior de Estudos Brasileiros was connected, in several fundamental points, with the developmentalism of Juscelino Kubitschek. President Kubitschek, when defending the importance of the country's economic development, always mentioned the need to link education to development. In the goals program, the education plan for development defended technical-professional education as a process consistent with Brazilian development. Considering the academic education of high school ineffective for young people in practical life, Juscelino urgently mentioned the adjustment of this level of education and, therefore, attributed fundamental importance to the capacity of qualified labor in the performance of the various sectors of economic production. In this way, professional education was present at all times, configuring itself as a primordial element for the promotion of economic development, according to the official proposal. The present work therefore intended to analyze and understand the relationships between economic and social policy, ideology and secondary education in the period 1956-61, precisely when the binomial development and vocational education began to become the ideology of the elites and their intellectuals for the Brazilian problem.
Developmentalism and education: secondary education in the period from 1956 to 1961
Keywords: Educação; Desenvolvimentismo; Política educacional; Ensino médio; Education; Developmentalism; Educational politics; High school; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM